PAJAK HOTEL: TARIF, PERHITUNGAN, PENYETORAN DAN PERHITUNGAN - Agusstina Sugita Benga Tokan Wato; Levi Martantina (Jurnal Bisnis Terapan, 2024)
The object of hotel tax imposed includes services provided by hotels whose payments include service such as Room Service and Food and Beverage as hotel equipment that provides comfort including sports facilities, entertainment and other accommodation. The hotel provides various service eithe the intention of obtaining revenue which will bw calculated on a daily, monthly and annual basis. The purpose of the preparation of this Final Report is to determine the application of Hotel Tax calculation and reporting at Gunawangsa Manyar Hotel Surabaya. Data collection techniques that the autor does includ interview techniques, observation dan documentation techniques, and literatur study techniques. The results Virtual Hotal Program (VHP), ar ini accordance with Surabaya City Regional Regulation Number 7 of 2023. The difference that occurred in April 2024 was the difference between Turnover Room Service revenue and Daily Revenue Report Room Service of Rp 59.504 resulting in a difference Hotel Nett Revenue, Service Charge, and Govenrment Tax. The nominal amount is the nominal Discount Food on Turnover Room Service which should be included in the Food Allowance on the Daily Revenue Report. This eror occurred because there were still transaction that had not been completed on that day, so, that at the time of withdrawing the Daily Revenue Report there were transaction that had not been accimulated perfectly. After resolving the difference, the next step is record transaction data in the Tax Surveillance Application. Recording this transaction data will produce electronic SPTPD which is used as hotel tax reporting. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License.